“With AIDS I am happier than I have ever been before” - Wardlow, Holly (The Australian journal of anthropology, 2019)
In her 2016 article Sherry Ortner discusses what she calls the rise of ‘dark anthropology’: that is, ethnographic work that analyses situations of domination, dispossession, and violence. She, like Joel Robbins (), posits as a counterpoint the emergence of ‘anthropologies of the good,’ which emphasise care and ethics. In this paper I put these two anthropological projects into generative tension through an analysis of HIV-positive women's lives in Papua New Guinea. In the first part of the paper I demonstrate the ways in which resource extraction has created vulnerabilities to HIV—in part through the coerced marriages of women to powerful landowners. In the second, I discuss ways in which the antiretroviral era has made possible unexpected forms of kindness towards HIV-positive women. I end the paper with a discussion of what HIV-positive women mean when they claim that they are happier now than in their pre-diagnosis lives.